2016
DOI: 10.1371/journal.pone.0151189
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus Laparoscopic Distal Pancreatectomy: A Meta-Analysis of Short-Term Outcomes

Abstract: AIMTo compare the safety and efficacy of robotic-assisted distal pancreatectomy (RADP) and laparoscopic distal pancreatectomy (LDP).METHODSA literature search of PubMed, EMBASE, and the Cochrane Library database up to June 30, 2015 was performed. The following key words were used: pancreas, distal pancreatectomy, pancreatic, laparoscopic, laparoscopy, robotic, and robotic-assisted. Fixed and random effects models were applied. Study quality was assessed using the Newcastle-Ottawa Scale.RESULTSSeven non-randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 29 publications
7
51
2
2
Order By: Relevance
“…Recent meta‐analyses demonstrated that the mean operation time in RDP and LDP was 247.8 and 229.9 min, respectively . Our study showed that RDP was not associated with longer mean operative times, although dock‐the‐robot and exchange instruments may take up to 12% of operative time during robotic pancreatic procedures .…”
Section: Discussionmentioning
confidence: 50%
“…Recent meta‐analyses demonstrated that the mean operation time in RDP and LDP was 247.8 and 229.9 min, respectively . Our study showed that RDP was not associated with longer mean operative times, although dock‐the‐robot and exchange instruments may take up to 12% of operative time during robotic pancreatic procedures .…”
Section: Discussionmentioning
confidence: 50%
“…An observed HR or OR > 1 implied a worse prognosis for the group with VM positivity, and it was considered statistically significant if the values of 95% confidence intervals did not overlap the value “1.” The heterogeneity of the included studies was evaluated by the χ 2 and I 2 tests, and P < 0.10 or I 2 > 50% was defined as heterogeneous. The fixed-effect model was used for merging the homogeneous data, and the random-effects model was suitable for merging the heterogeneous data as previously reported [26]. Publication bias was evaluated by Egger's test (STATA 14) with P < 0.05 indicating potential bias.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, a meta-analysis of short-term outcomes between LDP and robotic-assisted distal pancreatectomy (RADP) found a lower blood loss and a higher rate of spleen-preserving procedures in RADP. [31] Thus, the technological improvements and the magnified view during laparoscopy are crucial for control of bleeding. Nevertheless, lower rates of bleeding where found in a surgical series that excluded malignancies, suggesting a major role for the size and histology of the tumor.…”
Section: Discussionmentioning
confidence: 99%